The quality of governance and its impact on FDI inflows: A comparative study of EU member states - Bogusława Dobrowolska; Tomasz Dorożyński; Anetta Kuna-Marszałek (Comparative Economic Research. Central and Eastern Europe, 2023)
The principal goal of the article is to assess the quality of governance (QG) in the EU-28 over the period 2004-2020. It also examines the relationship between QG and FDI inward stock as a % of GDP. The study has been divided into five stages. The first one, based on the Worldwide Governance Indicators (WGI), attempts to identify countries that represent similar levels of institutional quality. Based on this criterion and using clustering methods, we divided the EU Member States into four groups. In the second step, we used the values of the synthetic index of QG to compare the level of institutional quality among the Member States between 2004 and 2020. The third step assesses FDI as a % of GDP in the Member States. Due to substantial differences, we divided them into four groups, arranged in ascending order of FDI as a % of GDP. In the fourth stage of the analysis, we examined the relationship between FDI as a share of GDP and groups of countries with similar QG. Finally, we examined the relevance of six individual dimensions of governance for FDI inflows in the EU-28 countries. The study demonstrates that the EU Member States differ significantly regarding the overall QG measured with the WGI. The results of the statistical analysis allow us to positively verify the hypothesis about a positive relationship between QG and the inflow of FDI. The most important partial variable is regulatory quality. The added value of this article comes from grouping the EU-28 based on the similarity of their quality of governance (measured by six dimensions of governance) and demonstrating that it impacts FDI inflows. We created a synthetic index of governance quality values to compare the level of institutional quality among the Member States between 2004 and 2020.
Keywords: F21; F23; 330; quality of governance; FDI; EU Member States; hierarchical cluster analysis